Age-Matched Comparative Analysis of Binocular Vision Anomalies among Children with Dyslexia in Northern Nigeria - Ismail Salma Mukhtar; Ngozika Esther Ezinne; Mizhanim Mohamad Shahimin; Bariah Mohd-Ali; Eki Oghre; Ferial M. Zeried; Uchechukwu Levi Osuagwu (MDPI AG, 2024)
Background: Dyslexia, a neurodevelopmental disorder affecting reading skills, poses significant challenges to children's academic performance and quality of life. Despite its rising prevalence and adverse effects, understanding of its relationship with vision anomalies remains limited, particularly in low-resource settings like Nigeria. This study aims to assess the prevalence of binocular vision anomalies (BVAs) among children with and without dyslexia in Kano, Nigeria. Methods: This is a hospital-based, cross-sectional, matched-paired, controlled study conducted at the Aminu Kano Teaching Hospital (AKTH) Eye Clinic in Northern Nigeria. The study included school children who visited the AKTH Eye Clinic from January 2018 to December 2022. Visual acuity tests, external eye examinations and accommodative, binocular vision and oculomotor skills tests were conducted. Descriptive statistics, independent t-tests, Mann-Whitney U tests and Fisher's exact tests were conducted, with a significance level set at p < 0.05. Results: Forty-four children aged 12 ± 2 years participated. Children with dyslexia reported higher rates of visual symptoms than those without dyslexia, Blurring vision, visual distortion and eye strain were the most prevalent (p < 0.05) BV symptoms. Accommodative insufficiency), was the most common visual abnormality, and was significantly higher in children with dyslexia than those without dyslexia (45.5% vs. 18.2%). However, other visual anomalies showed no significant difference between groups. There was a high prevalence of binocular vision anomalies in both groups. Binocular test findings showed dyslexic children had significantly lower distance positive fusional vergence recovery values (p = 0.005). All cases of convergence insufficiency alone were found in the non-dyslexic group. Conclusions: The study found that children with dyslexia residing in Northern Nigeria demonstrated higher rates of visual symptoms, more accommodative insufficiency and lower distance positive fusional vergence recovery values compared to their non-dyslexic counterparts.